The role of the rehabilitation in the prevention and treatment of obesity – an editorial article - Anna Golus; Marta Bielejewska; Dominika Ciecierska; Karolina Kuźba; Kamil Potyra; Wiktoria Śniegowska; Paweł Wojtczak; Anna Ziółkowska; Bartłomiej Wrzesiński; Edyta Piechocka (Journal of Education, Health and Sport, 2018)
Obesity according to the WHO is an epidemic of modern times, because it affects a large number of people in all age groups around the world. This disease itself makes it difficult for the patients suffering from it to function, but above all carries a lot of complications. These include diseases of the cardiovascular system, stroke, osteoarthritis, diseases of the digestive system. Obesity significantly increases the risk of death, which is why it is so important to start treatment as soon as possible. The most important goal of therapy is the reduction of body weight, which can only be achieved by combining a properly selected diet and physical activity. It is extremely important to choose the optimal training plan, because the fight against obesity will be effective only if patients increase daily energy expenditure.